2006
DOI: 10.1016/j.seizure.2006.03.005
|View full text |Cite
|
Sign up to set email alerts
|

A model of heart rate changes to detect seizures in severe epilepsy

Abstract: Heart rate patterns can be accurately characterized with a new developed curve-fitting algorithm. Heart rate changes can also be used for automatic detection of seizures in patients with severe epilepsy if the model parameters are chosen according to predefined characteristics of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
106
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 14 publications
3
106
0
6
Order By: Relevance
“…16 Severe tachycardia, a common feature of seizures in human patients, correlates with neuronal discharges and is a sensitive method for early detection of seizures in newborns and adult patients. [20][21][22][23][24] In newborn piglets, we observed a robust increase in HR concomitant with vasodilation of pial arterioles for the duration of the ictal episode. 7-10 Therefore, we compared the bicuculline-induced dynamics of HR as a reliable indicator of seizure activity in control and CORM-A1-treated piglets (Figure 3).…”
Section: Acute Effects Of Enteral Corm-a1 In Systemic and Cerebral CImentioning
confidence: 68%
See 1 more Smart Citation
“…16 Severe tachycardia, a common feature of seizures in human patients, correlates with neuronal discharges and is a sensitive method for early detection of seizures in newborns and adult patients. [20][21][22][23][24] In newborn piglets, we observed a robust increase in HR concomitant with vasodilation of pial arterioles for the duration of the ictal episode. 7-10 Therefore, we compared the bicuculline-induced dynamics of HR as a reliable indicator of seizure activity in control and CORM-A1-treated piglets (Figure 3).…”
Section: Acute Effects Of Enteral Corm-a1 In Systemic and Cerebral CImentioning
confidence: 68%
“…8 Alternatively, one may hypothesize that CO-derived CORM-A1 has anticonvulsant effects. However, CORM-A1 did not affect the dynamics of ictal tachycardia, a reliable and sensitive indicator of status epilepticus in patients, [20][21][22][23][24] of the EEG suggested that CO has proconvulsant, rather than anticonvulsant action. 16 Importantly, CORM-A1 (2 mg/kg), administered via enteral or parenteral routes, provides a safe and effective pharmacological option for prevention of oxidative stress-induced cerebral vascular disease.…”
Section: Discussionmentioning
confidence: 92%
“…In ADL, the use of PPG is for instance researched to detect PR changes in patients with epilepsy [20], as this can indicate seizures [21]. Susceptibility to motion hampers beat-to-beat analysis, e.g., to obtain pulse rate variability (PRV) [22], or to detect atrial fibrillation [23].…”
mentioning
confidence: 99%
“…Moreover, the autonomic imbalance in the regulation of cardiac functions is the leading mechanisms of sudden death in epilepsy [3,6]. Some authors suggest using parameters of heart rate as a biomarker refl ecting the risk of status epilepticus [5,10].The causal connection between the brain and the heart is evident [7-9], however, association of cardiovascular and CNS disorders with increasing convulsive readiness (CR) remains poorly understood. For this reason, the study of cardiovascular regulation at different levels of CR will clarify the role of each system and their interrelationship in provoking the pathological processes.…”
mentioning
confidence: 99%
“…Moreover, the autonomic imbalance in the regulation of cardiac functions is the leading mechanisms of sudden death in epilepsy [3,6]. Some authors suggest using parameters of heart rate as a biomarker refl ecting the risk of status epilepticus [5,10].…”
mentioning
confidence: 99%